I am the bread of life: imagery in John 6:32-51 - J. G. van der Walt (Acta Theologica)
John 6 is one of the most discussed chapters in the Gospel according to John, because of the Eucharistic nature of the language in 6:51c-59. The complex nature of the metaphors and imagery used in these verses, as well as the richness and power of the ensuing communication, are often overlooked. This article explores the literary nature of the text and focuses on the dynamics of metaphor, the interaction between the figurative and literal sections in the text, as well as the strong influence of the socio-religious context of the text on its interpretation and understanding.